Genome-based characterization of Listeria monocytogenes, Costa Rica - Giralt-Zúñiga, María; Redondo-Solano, Mauricio; Moura, Alexandra; Tessaud-Rita, Nathalie; Bracq-Dieye, Hélène; Vales, Guillaume; Thouvenot, Pierre; Leclercq, Alexandre; Chaves-Ulate, Carolina; Núñez-Montero, Kattia; Guillén-Watson, Rossy; Rivas-Solano, Olga; et al. (Emerging Infectious Diseases 2023, 2023)
Genomic data on the foodborne pathogen Listeria monocytogenes from Central America are scarce. We analyzed 92 isolates collected during 2009–2019 from different regions in Costa Rica, compared those to publicly available genomes, and identified unrecognized outbreaks. Our findings suggest mandatory reporting of listeriosis in Costa Rica would improve pathogen surveillance.
Artículo.
Keywords: Listeria monocytogenes; Datos genómicos; Patógenos; Virosis; Evaluación de riesgos -- Virus; Secuenciación -- Genoma; Producción -- Quesos; Enfermedades infecciosas -- Genotipos; Genomic data; Pathogens; Viral diseases; Risk assessment -- Viruses; Sequencing -- Genome; Production -- Cheeses; Infectious diseases -- Genotypes; Research Subject Categories::MEDICINE::Microbiology, immunology, infectious diseases::Infectious diseases; Research Subject Categories::NATURAL SCIENCES::Biology